Ovariectomized hypertensive rats submitted to exercise and estrogen therapy present improved levels of angiotensin receptors in the aorta (Research, Society and Development, 2025)
The renin-angiotensin system (RAS) and the antioxidant system play integral and interconnected roles in finely regulating cardiovascular function during exercise training and estrogen level alterations. This study aimed to investigate whether training modulates RAAS receptors and antioxidant proteins in a manner similar to 17β-estradiol (E2) therapy in the aorta of ovariectomized spontaneously hypertensive rats (SHR). Animals were divided into Sham (SH), Ovariectomized (OVX), OVX+ET (OE2), OVX+swimming (OSW) and OVX+ET+swimming (OE2+SW) groups. ET entailed the administration of 5 µg 17β-estradiol three times per week. Swimming was performed for one hour/day, five times per week. Two days after the last treatment and/or training session, systolic blood pressure was assessed. Protein content from isolated aorta was analyzed by western blot for the RAS receptors (angiotensin AT1-receptor - AT1R, angiotensin AT2-receptor - AT2R, and Mas receptor - Mas), endothelial nitric oxide synthase (eNOS), total and phosphorylated Protein Kinase B at Ser473 (p-AktSer473), Superoxide Dismutase 2 (SOD 2) and ß-actin. The results showed that AT1R was increased only in the OVX group, while angiotensin AT2R and Mas increased in both OSW and OE2+SW. In addition, ET therapy increased both eNOS and SOD 2  levels in SH, OE2 and OE2+SW. Interestingly, p-AktSer473 levels increased similarly in the same groups observed for eNOS. This study provided mechanistic evidence suggesting that both physical and hormonal interventions act via the protective RAS by stimulating the p-AktSer473-eNOS and SOD 2 pathways, which can be associated with vasodilation and potential antioxidant capacity in estrogen deficiency conditions.